The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1111/j.1365-2257.1997.tb00008.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of oral anticoagulant control by a nurse-practitioner using a computer decision-support system with that by clinicians

Abstract: With increasing work-loads in anticoagulant clinics different methods of service delivery need evaluation. The quality of anticoagulant control achieved by a nurse-practitioner using a computer decision-support system (CDSS) was compared with that achieved by trainee doctors without CDSS. Eighty-one out-patients (group A, therapeutic range 2-3) and 96 out-patients (group B, therapeutic range 3-4.5) were randomized to management by a nurse-practitioner or by trainee doctors (clinicians). Thirty-seven patients i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 7 publications
0
24
0
Order By: Relevance
“…More extensive use of computer-based algorithms for does adjustment of anticoagulants could help avoid systemic underanticoagulation. [42][43][44][45][46] We found that the relative risk of thromboembolic events increased significantly when the international normalized ratio exceeded 5. This reflects the curvilinear association between ratio levels and risk of thromboemboli that we identified in 7 of 16 studies included in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…More extensive use of computer-based algorithms for does adjustment of anticoagulants could help avoid systemic underanticoagulation. [42][43][44][45][46] We found that the relative risk of thromboembolic events increased significantly when the international normalized ratio exceeded 5. This reflects the curvilinear association between ratio levels and risk of thromboemboli that we identified in 7 of 16 studies included in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…20 This study was not powered to detect equivalence. The study compared Both triage studies assessed the impact of CDSS in terms of performance measures and patient outcomes.…”
Section: Cdss (4 Rcts 1 Its 19744 Participants)mentioning
confidence: 97%
“…18,23 In three RCTs, the targeted behaviour was anticoagulation management. 18,20,24 Characteristics of these studies are given in Table 4 and the results are reported in Table 5.…”
Section: Cdss (4 Rcts 1 Its 19744 Participants)mentioning
confidence: 99%
“…The variation from the dose suggested by the software was 35%, which is higher than the 25% found by Vadher et al when they studied nurses using CDSS. 8 However, it is less than the 43% gap found when doctors' decisions were compared with that suggested by the CDSS.…”
Section: Discussionmentioning
confidence: 95%
“…Where comparison has been made between nurses using computerised decision support and junior doctors using clinical judgement, the nurses achieved better control for patients with an INR target ratio of 2-3, and as good control as the doctors when target INR is 3-4.5. 8 A primary care organisation (PCO) recognised the potential benefits of a practice-based anticoagulation service and implemented it across 13 practices, deciding that practice nurses would be the appropriate professional group to deliver the service. They put on a training course comprising the relevant biomedicine: how anticoagulants work, the patients who need it and for how long, interactions and safety issues.…”
Section: Refereed Papersmentioning
confidence: 99%